Du Retour à Reims au Retour des classes sociales - Paul Bouffartigue (La Nouvelle Revue du Travail, 2013)
With Retour à Reims [“Return to Reims”], which is published in 2009, Didier Eribon used his own biographical experience to talk about the working-class world he left behind; transformations in working classes; the domination of class; and how academic success helped him to get a sense for this state of affairs and argue against it. The book’s presentation is an occasion to discuss a grid of sociological analysis inspired from the work of Pierre Bourdieu, along with topical questions such as social class and social mobility.